Bench-scale study of the effect of phosphate on an aerobic iron oxidation plant for mine water treatment - Tischler, Judith S.; Wiacek, Claudia; Janneck, Eberhard; Schlömann, Michael (Water research (Oxford), 2014)
At the opencast pit Nochten acidic iron- and sulfate-rich mine waters are treated biotechnologically in a mine-water treatment plant by microbial iron oxidation. Due to the low phosphate concentration in such waters the treatment plant was simulated in bench-scale to investigate the influence of addition of potassium dihydrogen phosphate on chemical and biological parameters of the mine-water treatment. As a result of the phosphate addition the number of cells increased, which resulted in an increase of the iron oxidation rate in the reactor with phosphate addition by a factor of 1.7 compared to a reference approach without phosphate addition. Terminal restriction fragment length polymorphism (T-RFLP) analysis during the cultivation revealed a shift of the microbial community depending on the phosphate addition. While almost exclusively iron-oxidizing bacteria related to “Ferrovum” sp. were detected with phosphate addition, the microbial community was more diverse without phosphate addition. In the latter case, iron-oxidizing bacteria (“Ferrovum” sp., Acidithiobacillus spp.) as well as non-iron-oxidizing bacteria (Acidiphilium sp.) were identified. [Display omitted] •Simulation of biological remediation of acid mine waters in bench-scale.•Optimization of bioremediation of acid mine waters by phosphate addition.•Limitation of “Ferrovum” spp. by phosphate in acid mine waters.